Inductive * -Semirings - Ésik, Zoltán; Kuich, Werner (BRICS Report Series, 2000)
One of the most well-known induction principles in computer science is the fixed point induction rule, or least pre-fixed point rule. Inductive *-semirings are partially ordered semirings equipped with a star operation satisfying the fixed point equation and the fixed point induction rule for linear terms. Inductive *-semirings are extensions of continuous semirings and the Kleene algebras of Conway and Kozen. We develop, in a systematic way, the rudiments of the theory of inductive *-semirings in relation to automata, languages and power series. In particular, we prove that if S is an inductive *-semiring, then so is the semiring of matrices Sn*n, for any integer n >= 0, and that if S is an inductive *-semiring, then so is any semiring of power series S((A*)). As shown by Kozen, the dual of an inductive *-semiring may not be inductive. In contrast, we show that the dual of an iteration semiring is an iteration semiring. Kuich proved a general Kleene theorem for continuous semirings, and Bloom and Esik proved a Kleene theorem for all Conway semirings. Since any inductive *-semiring is a Conway semiring and an iteration semiring, as we show, there results a Kleene theorem applicable to all inductive *-semirings. We also describe the structure of the initial inductive *-semiring and conjecture that any free inductive *-semiring may be given as a semiring of rational power series with coefficients in the initial inductive *-semiring. We relate this conjecture to recent axiomatization results on the equational theory of the regular sets.